RESEARCH AND DEVELOPMENT OF ADDITIVE TECHNOLOGY IN INDUSTRIAL MANUFACTURING OF NEW PRODUCTS IN KAZAKHSTAN - Mukhamadeyeva, Railya (International Journal of Research -GRANTHAALAYAH, 2019)
The main goal of the project is to investigate the possible ways of introducing the additive technologies, to study the peculiarities of the layer wise synthesis process when producing foundry patterns and defining basic parameters which influence the quality of the produced parts. Based on the analysis of the results of activities aimed at the development of three-dimensional printing in Kazakhstan, highlighted the alleged problems of the successful implementation of additive technologies in the economy and in education particularly. In article the scheme of the existence and development of new technologies and the role of government’s support in the process is given. The results of data analysis from the Internet shows that there is a sufficient number of three-dimensional modeling laboratories, but it is mostly commercial service companies in the field of three-dimensional printing. The key factor in the growth of any economy is to organize an effective system of technology transfer and its further improvement.